Lichen chemistry is concordant with multilocus gene genealogy in the genus Cetrelia (Parmeliaceae, Ascomycota). Issue 2 (February 2019) - Mark, Kristiina; Randlane, Tiina; Thor, Göran; Hur, Jae-Seoun; Obermayer, Walter; Saag, Andres
Abstract: The lichen genus Cetrelia represents a taxonomically interesting case where morphologically almost uniform populations differ considerably from each other chemically. Similar variation is not uncommon among lichenized fungi, but it is disputable whether such populations should be considered entities at the species level. Species boundaries in Cetrelia are traditionally delimited either as solely based on morphology or as combinations of morpho- and chemotypes. A dataset of four nuclear markers (ITS, IGS, Mcm7, RPB1) from 62 specimens, representing ten Cetrelia species, was analysed within Bayesian and maximum likelihood frameworks. Analyses recovered a well-resolved phylogeny where the traditional species generally were monophyletic, with the exception of Cetrelia chicitae and Cetrelia pseudolivetorum . Species delimitation analyses supported the distinction of 15 groups within the studied Cetrelia taxa, dividing three traditionally identified species into some species candidates. Chemotypes, distinguished according to the major medullary substance, clearly correlated with clades recovered within Cetrelia, while samples with the same reproductive mode were dispersed throughout the phylogenetic tree. Consequently, delimiting Cetrelia species based only on reproductive morphology is not supported phylogenetically. Character analyses suggest that chemical characters have been more consistent compared to reproductive mode and indicate that metabolite evolution in Cetrelia towards more complex substances is probable. Highlights: A well-resolved multilocus phylogeny was recovered in lichen genus Cetrelia. Chemotypes based on secondary compounds clearly correlated with gene genealogy. Species of the same reproductive mode were dispersed throughout phylogenetic tree. Delimiting Cetrelia species by combining morpho- and chemotypes is partly supported. Chemical evolution in Cetrelia has probably been towards more complex substances.